Epigenetics and Early Life Stress: Experimental Brood Size Affects DNA Methylation in Great Tits (Parus major) - Sepers, Bernice; Erven, Jolijn A. M.; Gawehns, Fleur; Laine, Veronika N.; van Oers, Kees (Frontiers in Ecology and Evolution, 2021)
Early developmental conditions are known to have life-long effects on an individual’s behavior, physiology and fitness. In altricial birds, a majority of these conditions, such as the number of siblings and the amount of food provisioned, are controlled by the parents. This opens up the potential for parents to adjust the behavior and physiology of their offspring according to local post-natal circumstances. However, the mechanisms underlying such intergenerational regulation remain largely unknown. A mechanism often proposed to possibly explain how parental effects mediate consistent phenotypic change is DNA methylation. To investigate whether early-life effects on offspring phenotypes are mediated by DNA methylation, we cross-fostered great tit (Parus major) nestlings and manipulated their brood size in a natural study population. We assessed genome-wide DNA methylation levels of CpG sites in erythrocyte DNA, using Reduced Representation Bisulfite Sequencing (RRBS). By comparing DNA methylation levels between biological siblings raised in enlarged and reduced broods and between biological siblings of control broods, we assessed which CpG sites were differentially methylated due to brood size. We found 32 differentially methylated sites (DMS) between siblings from enlarged and reduced broods, a larger number than in the comparison between siblings from control broods. A considerable number of these DMS were located in or near genes involved in development, growth, metabolism, behavior and cognition. Since the biological functions of these genes line up with previously found effects of brood size and food availability, it is likely that the nestlings in the enlarged broods suffered from nutritional stress. We therefore conclude that early-life stress might directly affect epigenetic regulation of genes related to early life conditions. Future studies should link such experimentally induced DNA methylation changes to expression of phenotypic traits and assess whether these effects affect parental fitness to determine if such changes are also adaptive.